Docufictions : essays on the intersection of documentary and fictional filmmaking - Rhodes, Gary Don; Springer, John Parris; Lipkin, Steven N.; Paget, Derek; Roscoe, Jane; Bould, Mark; Green, Jared F.; Levin, Donald; Humphries, Reynold; Lee, Michael; Bentin, Doug; Bayer, Gerd; et al. (Jefferson, N.C. : McFarland & Co., 2005)
"These 18 essays examine the relationships between narrative fiction films and documentary filmmaking. Topics include the docudrama in early cinema, the industrial film as faux documentary, the fear evoked in 1950s science fiction films, the selling of "reality" in mockumentaries, and reality television and documentary forms"--Provided by publisher.
18. The Future of Documentary? "Conditional Tense" Documentary and the Historical Record / Paul Ward
Bibliografske bilješke uz pojedine radove. - Kazalo
Keywords: Documentary-style films -- History and criticism; dokumentarna drama; film -- dokumentarni stil